Security enhancement on vehicle communication networks - Song, Xiaohui (2016)
Vehicular Ad Hoc Networks (VANETs) are special type of mobile ad hoc networks (MANETs). The vehicles can form a self-organized wireless network for data exchange. Base on the VANETs, the traffic congestion, the road and weather conditions, and so on, all can be broadcasted to others. Then the drivers can enjoy driving comfort; The Transport Agency can manage the traffic much easier and come out a better road design; the law enforcement agency also can trace all the messages to their senders, when necessary. Referring to above description, we can make a conclusion that the messages must be sent securely and quickly. Otherwise, the messages, which are sent by the hacker, can cause inestimable harm to the traffic system. The driver and Transport Agency may make wrong decision through the slow information. To address this concern, we must propose a Vehicle Communication Network, which can make sure that the messages are reliability, integrity and timeliness.